2021
DOI: 10.32718/nvlvet-f9608
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the introduction of rice bran on fermented milk drink

Abstract: Rice bran is an agro-industrial waste with excellent nutritional value and a considerable content of bioactive compounds. Biotransformation processes by fermented milk drink fermentation increase the interest in obtaining products from agro-industrial wastes with good biological properties. The viability of introducing rice bran (RB) into fermented milk drinks to improve the structural stability and sensory was studied. Fermented milk drink supplemented with 0, 0.1 %, 0.3 %, 0.5 %, 0.7 % amount of RB were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Phenolic compounds have antioxidant potential and scavenge harmful free radicals in the body, reducing oxidative stress [148][149][150][151][152]. They also show antihypertensive, nutritional and physiochemical properties that promote physicochemical and functional properties [152][153][154][155][156] (Table 4). Today, many by-products derived from cereal processing have reach as dietary supplements or ingredients in fermented functional beverages [1 tion is a cheap biotechnological process used worldwide and is also one of t cesses used for food preservation and the elaboration of food products as b various cereals worldwide [140][141][142].…”
Section: Cereal Wastementioning
confidence: 99%
See 2 more Smart Citations
“…Phenolic compounds have antioxidant potential and scavenge harmful free radicals in the body, reducing oxidative stress [148][149][150][151][152]. They also show antihypertensive, nutritional and physiochemical properties that promote physicochemical and functional properties [152][153][154][155][156] (Table 4). Today, many by-products derived from cereal processing have reach as dietary supplements or ingredients in fermented functional beverages [1 tion is a cheap biotechnological process used worldwide and is also one of t cesses used for food preservation and the elaboration of food products as b various cereals worldwide [140][141][142].…”
Section: Cereal Wastementioning
confidence: 99%
“…Good physicochemical and antimicrobial properties [154] Multigrain beverage Barnyard, foxtail kodo (phenolic compounds) Prebiotic activity, low GI (glycemic index), high antioxidant activity in beverage [148] Fermented beverages Rice bran (protein and dietary fiber) Higher sensory acceptance, best shelf life and nutritional value [155] Tea Corn tassel (phenolic compounds)…”
Section: Type Of Beverage Waste Food Ingredient Functionality Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Defatted sesame cake is rich in dietary fiber, and it was found to significantly improve the viscosity, number of probiotics and antioxidant activity of kefir, which are excellent qualities of kefir products. The paper [14] presented the influence of introducing fiber-rich bran on the quality of kefir. The results showed that adding RB to kefir can significantly increase pH and decrease acidity.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%